Pengaruh Personalitas (Dark Triad), Religiusitas-Spiritualitas Terhadap Niat Kewirausahaan Pada Remaja Di DKI Jakarta - Mart, Fakhruddin; Mulyadi, Rizki; Zahra, Indira (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
The participation of young people in the Creative Economy Sector is needed. Amid the effects of the pandemic, which is the effect of the global economic downturn, the results of a recent survey on May 14-20 2020 of American teenagers showed that teenagers remain open to becoming entrepreneurs and starting businesses. The question is about how the intention to become entrepreneurial in Indonesian youth, especially in DKI Jakarta. In this case, we focus on research on how the influence of personality, religiosity, and spirituality as well as entrepreneurial self-efficacy affects entrepreneurial intentions. Data from a sample of 215 adolescents from schools in Central Jakarta and West Jakarta were then processed using the Structure Equation Model (SEM) technique through the use of SmartPLS3 software. The results show that Machiavellianism does not have a significant effect, in contrast to narcissism which has a positive effect, and psychopathy which has a greater negative effect on entrepreneurial intentions than the positive influence of religious activity and faith-based coping on entrepreneurial intentions. This study concluded that psychopathic personality has a direct negative effect on entrepreneurial intention. Meanwhile, narcissism, religious activities, and faith-based coping have a positive effect on entrepreneurial intentions, but entrepreneurial self-efficacy is needed as a mediator for religious activities to have a better effect on the entrepreneurial intention of adolescents in DKI Jakarta